The Legal Legitimacy of the East Java Indonesian Ulema Council (MUI) Fatwas on COVID-19 in the Regulation of Religious Practices During the COVID-19 Pandemic - Muhammad Noor Harisudin; Rohmad Agus Solihin (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2023)
The COVID-19 pandemic has brought about significant social changes that have affected the religious practices of Muslims, particularly in the implementation of worship involving direct interaction within the community. This situation prompted the Indonesian Ulema Council (Majelis Ulama Indonesia/MUI) of East Java Province to issue a series of fatwas as guidelines for Muslims in carrying out religious activities during the pandemic, while maintaining a balance between adherence to Islamic law and the protection of public health. This study aims to analyze the fatwas issued by the East Java Provincial MUI concerning the COVID-19 pandemic and to examine the legal reasoning (istinbāṭ al-aḥkām) employed in formulating these fatwas. This research adopts a qualitative approach using a descriptive qualitative method, with data collected from fatwa documents, relevant academic literature, and applicable legal regulations. The findings reveal that the East Java Provincial MUI issued five major fatwas concerning the use of the AstraZeneca vaccine, COVID-19 testing during fasting, face-to-face learning, the implementation of Friday prayers in two consecutive sessions, and the management of Muslim bodies infected with COVID-19. The fatwas were formulated through both the qauli and manhaji approaches by taking into account the principles of maslahah mursalah, maqāṣid al-sharī‘ah, and prevailing social conditions. These fatwas emphasize the protection of human life (ḥifẓ al-nafs), the prevention of harm, and the realization of public welfare. Consequently, they provide adaptive, contextual, and responsive religious legal guidance in addressing the global health crisis while reinforcing the role of fatwas as instruments of Islamic law in responding to contemporary legal issues.